Changes in Sexual Activity Patterns Before and During Pregnancy Among Women in a Rural Community - Diana Puspitasari; Yusri Dwi Lestari; Wiwin Nur Siam (Genius Journal of Nursing, 2025)
Introduction: Pregnancy is associated with various physiological and psychological changes that may influence women’s sexual activity patterns, particularly during the first and third trimesters. Some women experience decreased sexual desire, while others may report increased sexual interest during pregnancy.Objectives: This study aimed to examine differences in sexual activity patterns before and during pregnancy among women in a rural community.Methods: This study employed a comparative design with a pre–post approach. The sample consisted of 20 pregnant women selected using a total sampling technique. Data were collected using structured questionnaires and analyzed using the paired t-test with a significance level of p < 0.05.Results: The findings revealed a statistically significant difference in sexual activity patterns before and during pregnancy (p < 0.001), indicating that pregnancy significantly influences sexual activity among women.Conclusions: There is a significant difference in sexual activity patterns before and during pregnancy. These findings highlight the importance of providing appropriate education and counseling regarding sexual health during pregnancy to support maternal well-being.